Comparison of methods of dna extraction from giardia spp. Measured by conventional PCR [Comparación de métodos de extracción de adn de giardia spp. Medidos por PCR convencional] - Tarqui-Terrones K. (2019)
Objectives. To compare different methods of DNA extraction from cysts and trophozoites of Giardia spp. using the conventional polymerase chain reaction (PCR) technique. Materials and Methods. Cysts of Giardia spp. were isolated from 65 coprological samples from national reference hospitals, obtaining an average load of 5x104 parasites. In addition, Giardia intestinalis trophozoites (ATCC® 30957™) were cultured obtaining a 5x106 parasitic load. Eleven extraction methods for cysts and six for trophozoites were compared. The concentration and purity of the extracted DNA were determined by spectrophotometry and the extraction yield was assessed by amplification of the ß-giardin (bg) and glutamate dehydrogenase (gdh) genes with a semi nested PCR assay. Results. It was observed that method 1 showed the highest concentration of DNA from cysts (12.24 ng/µL), purity (1.4) and best performance (bg: 100% amplification; gdh: 60% amplification) compared to the other methods evaluated. In the case of trophozoites, the method without pre treatment showed the highest level of DNA concentration, purity, and yield (26.56 ng/µL; 1.85; 100% amplification of bg and gdh, respectively). Conclusions. Mechanical, thermal shock, and enzymatic pre-treatments are necessary for the rupture of the cystic wall of Giardia spp. making it the highest-yielding bg molecular marker for detecting cyst DNA. Trophozoites do not require pre-treatment to achieve satisfactory results. A reproducible methodology for the extraction of DNA from Giardia spp. from any evolutionary stage is available. © 2019, Instituto Nacional de Salud. All rights reserved.